Propylene Glycol Toxicity in Adolescent with Refractory Myoclonic Status Epilepticus - Kara A. Bjur; Bryan C. Cannon; Anthony L. Fine; Matthew J. Ritter; Kerry E. Schueler; Michael E. Nemergut (Case Reports in Pediatrics)
Propylene glycol (PG) is a solvent commonly used in medications that, while benign at low doses, may cause toxicity in adults and children at high doses. We describe a case and the physiologic sequelae of propylene glycol toxicity manifested in a critically ill adolescent male with refractory myoclonic status epilepticus aggressively treated with multiple PG-containing medications (lorazepam, phenobarbital, and pentobarbital)—all within accepted dosing guidelines and a total daily PG exposure previously recognized to be safe. Hemodynamic measurements by bedside echocardiography during clinical toxicity are also reported. Clinicians should have a high index of suspicion for propylene glycol toxicity in patients treated with PG-containing medications even when the total PG exposure is lower than currently accepted limits.